Dietary habits and incidence of adenomas and carcinomas in colonoscopy screening of people aged 65+ - Szamocka, Małgorzata; Meder, Agnieszka; Ameryk, Monika Anna; Milejczak, Marta; Świątkowski, Maciej (Journal of Education, Health and Sport, 2017)
Introduction. Colonoscopy screening for the early detection of colorectal cancer (CRC), despite many limitations, is widely used in the prevention of this most common digestive tract malignancy due to some important advantages. CRC is a nutrition-dependent disease. It is estimated that implementing rational nutrition as part of health promotion activities during childhood and continuing it in the adult life could reduce the morbidity and mortality of colon and rectal cancer. The aim of the study was to assess the effect of dietary habits on the incidence of colorectal adenomas and cancers in the population aged 65+ subjected to colonoscopy screening. Methods. The study method was standard colonoscopy screening conducted in subjects aged 65+ in whom no clinical signs of CRC were observed. The subjects were also assessed for their nutrition and the frequency of consumption of selected products, including red meat, vegetables, fruit and fried foods, using a standardized questionnaire prepared in cooperation with the Department of Nutrition and Dietetics, Collegium Medicum in Bydgoszcz, Poland. Results. Most CRC detections and the greatest number of excised adenomas were reported in subjects consuming vegetables as rarely as several times per year. Conclusions. Consumption of vegetables, among other foods, as part of rational nutrition from childhood through adult life may reduce the morbidity and mortality due to CRC.